2020
DOI: 10.1016/j.msard.2020.102359
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to social distancing and use of personal protective equipment and the risk of SARS-CoV-2 infection in a cohort of patients with multiple sclerosis

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
0
12
1
Order By: Relevance
“…Finally, the results of survey research in Italy may help explain why some groups of people with disabilities living in the community may have been less exposed to a COVID-19 infection. The study showed generally good adherence of persons with Multiple Sclerosis ( n = 551) to lockdown and extensive use of protection devices, as measured by Lockdown Scores [ 65 ]. Overall, the authors found that women, older persons, persons with disabilities, and those who were unemployed had higher Lockdown Scores ( p < 0.05) [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the results of survey research in Italy may help explain why some groups of people with disabilities living in the community may have been less exposed to a COVID-19 infection. The study showed generally good adherence of persons with Multiple Sclerosis ( n = 551) to lockdown and extensive use of protection devices, as measured by Lockdown Scores [ 65 ]. Overall, the authors found that women, older persons, persons with disabilities, and those who were unemployed had higher Lockdown Scores ( p < 0.05) [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study showed generally good adherence of persons with Multiple Sclerosis ( n = 551) to lockdown and extensive use of protection devices, as measured by Lockdown Scores [ 65 ]. Overall, the authors found that women, older persons, persons with disabilities, and those who were unemployed had higher Lockdown Scores ( p < 0.05) [ 65 ]. It is possible though, that this can arise from the combination of greater cautions due to the fear of the greater health consequences of an infection as well as lower social participation levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, specially trained support workers can be made available 24/7 from a simple contact mechanism, either for planned or unplanned needs of PwD [ 74 ]. Support provided can include the delivery of basic goods (e.g., medications, food) at home [ 47 , 53 , 89 ]. Buzzers, alarms, helplines as well as emergency contact numbers might be available for PwD to use them in emergencies (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…[75] Support provided can include the delivery of basic goods (e.g., medications, food) at home. [48,54,90] Buzzers, alarms, helplines as well as emergency contact numbers might be available for PwD to use them in emergencies (e.g. falls, acute disease, maltreatment, or abuse).…”
Section: Assure Contingency Assistance For Community-dwelling Pwdmentioning
confidence: 99%